Preparation method of perovskite single crystal film

By introducing self-assembled single-layer Meo-2PACz in the preparation of perovskite single-crystal films and embedding the PTAA layer, the problems of interface defects and uneven carrier transmission are solved, and a higher quality perovskite single-crystal films are achieved. and improved optoelectronic device performance.

CN119491294APending Publication Date: 2025-02-21HARBIN INSTITUTE OF TECHNOLOGY (SHENZHEN) (INSTITUTE OF SCIENCE AND TECHNOLOGY INNOVATION HARBIN INSTITUTE OF TECHNOLOGY SHENZHEN)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411573910.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

In the existing preparation method of perovskite single crystal thin film, the hydrophobic hole transport layer causes interface defects and unbalanced carrier transport, affecting device performance.

Method used

Self-assembled single layer Meo-2PACz is introduced and embedded in polymer PTAA to form a multi-layer structure by spin coating, which enhances the functionalization of the substrate surface and promotes the lateral growth and interface quality of the perovskite single crystal film.

Benefits of technology

It effectively suppresses interface defects and carrier losses, optimizes carrier transmission, and improves the quality of perovskite single crystal thin film and the performance of optoelectronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119491294A_ABST
    Figure CN119491294A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a perovskite single crystal film, and relates to the technical field of perovskite. The invention relates to a preparation method of a perovskite single crystal thin film, which comprises the following steps of: (1) spin-coating an ITO (Indium Tin Oxide) substrate with an Meo-2PACz molecular solution dissolved in an organic solvent 1, and annealing at 95-100 DEG C for 10-12 minutes to obtain a multi-layer Meo-2PACz small molecular thin film; and (2) spin-coating a PTAA solution dissolved in an organic solvent 2 on the multi-layer Meo-2PACz micromolecular film, and annealing at 95-100 DEG C for 10-12 minutes. According to the preparation method, the growth substrate of the single crystal is modified, and the prepared ITO / SAM / PTAA-SAM substrate has the advantages of optimizing the energy level, passivating interface defects, promoting carrier transport, providing perovskite nucleation sites and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of perovskite, and in particular to a method for preparing a perovskite single crystal film. Background Art

[0002] The spatially limited growth of perovskite single crystal thin film (PVK-SCTF) mainly utilizes the spacing between the upper and lower substrates to obtain growth space, thereby limiting the vertical growth of the crystal and achieving the ideal film thickness. The main steps include: 1. The cleaned ITO glass is cleaned in deionized water, acetone and isopropanol solvents for 10 minutes, and then subjected to UV hydrophilic treatment; 2. A certain solubility of polymer molecule PTAA is dissolved in chlorobenzene and spin-coated on the ITO glass and annealed to form a hydrophobic hole transport layer; 3. The uniformly dissolved perovskite precursor solution is added to the substrate spin-coated with PTAA, and then another substrate treated in the same way is covered; 4. The heating platform is heated from 70°C to 110°C at a certain heating rate.

[0003] The growth of PVK-SCTF is carried out on the relatively hydrophobic hole transport layer PTAA. This hydrophobic property ensures the lateral transmission of ions in the precursor liquid between the liquid films. However, the low surface energy caused by this hydrophobic property, coupled with the weak interaction between perovskite and PTAA, leads to insufficient nucleation sites on the surface of PTAA, making it difficult for the entire surface of the growing crystal to have a good fit with the growth substrate. This will lead to a high roughness and defect density on the buried interface of the perovskite single crystal, which will further have an adverse effect on the preparation of the device. Suppressing the formation of defects on the surface of the single crystal has become a difficulty and pain point that must be solved. In addition, the maximum value of the valence band of the hole transport layer PTAA is about -5.10eV, which has a large energy level barrier with ITO glass (-4.6eV), which will be unfavorable for the transmission of carriers between interfaces, resulting in the loss of device efficiency due to uneven carrier transmission. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a perovskite single crystal film. The present invention introduces a self-assembled monolayer (SAM) Meo-2PACz and functionalizes the substrate surface by embedding it into a polymer PTAA, thereby promoting the anisotropic lateral growth of SCTFs and suppressing defects and voids at the buried interface.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] The present invention provides a method for preparing a perovskite single crystal thin film, comprising the following steps:

[0007] (1) Spin coating a Meo-2PACz molecular solution dissolved in an organic solvent 1 on an ITO substrate, and annealing at 95-100° C. for 10-12 min to obtain a multilayer Meo-2PACz small molecule film;

[0008] (2) Spin-coat the PTAA solution dissolved in organic solvent 2 onto the multilayer Meo-2PACz small molecule film and anneal at 95-100° C. for 10-12 min.

[0009] The present invention forms a multi-layer Meo-2PACz small molecule film on an ITO substrate by spin coating a Meo-2PACz molecular solution, wherein the phosphate groups in the bottom Meo-2PACz small molecules have a strong anchoring effect with the ITO substrate and form an orderly arranged single molecule film, and the remaining Meo-2PACz molecules not involved in the anchoring are accumulated on the anchored single molecule film in a disordered form. In addition, the unanchored multi-layer Meo-2PACz molecules can be nested in the PTAA layer, which not only maintains the hydrophobicity of the PTAA layer, but also enhances the interaction between the perovskite single crystal film and the substrate by introducing a self-assembled monolayer (SAM), which is beneficial to suppressing the interface carrier loss while retaining the advantages of PTAA.

[0010] Preferably, in step (1), the concentration of the Meo-2PACz molecular solution is 0.5-5 mg / mL.

[0011] If the concentration of Meo-2PACz molecules is too low (less than 0.5 mg / mL), the coverage of the molecules on the ITO surface will be insufficient, affecting the uniformity of the work function distribution on the substrate surface and thus affecting the device performance; if the concentration of small molecules is too high (greater than 5 mg / mL), it will easily lead to uneven distribution of SAM in the PTAA layer, and it is easy to agglomerate in one position, affecting the roughness of the PTAA layer surface and the contact with the perovskite buried interface, affecting the transport of carriers.

[0012] More preferably, the concentration of the Meo-2PACz molecular solution is in the range of any one or both of 0.5 mg / mL, 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL, and 5 mg / mL.

[0013] Preferably, in step (1), the ITO substrate is UV pretreated.

[0014] Preferably, in step (1), the rotation speed during spin coating is 2000-3000 rpms, and the spin coating time is 20-30s.

[0015] Preferably, the organic solvent 1 includes ethanol or isopropanol, and the organic solvent 2 includes chlorobenzene or toluene.

[0016] Preferably, in step (2), the concentration of the PTAA solution is 1-5 mg / mL.

[0017] More preferably, the concentration of the PTAA solution is in the range of any one or both of 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL, and 5 mg / mL.

[0018] Preferably, in step (2), the rotation speed during spin coating is 4000-5000 rpms, and the spin coating time is 25-30 s.

[0019] Preferably, in step (2), the molecular weight of the PTAA is 5000-25000.

[0020] If the molecular weight of PTAA is too small (less than 5000), the hydrophobicity of the substrate is insufficient and the crystal surface is easily corroded by residual solvents. If the molecular weight of PTAA is too large (greater than 25000), the roughness of the PTAA film will increase, which is not conducive to the growth of single crystals.

[0021] More preferably, the molecular weight of the PTAA is within the range of any one or both of 5000, 6000, 7000, 8000, 9000, 10000, 15000, 20000, and 25000.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention introduces a self-assembled monolayer Meo-2PACz for passivation of SCTF interface defects and functionalizes the substrate surface by embedding it into a polymer PTAA. Since the substrate maintains sufficient hydrophobicity for ion transfer and protects Meo-2PACz molecules that are not firmly anchored to ITO in a high-temperature solution during the single crystal crystallization process, nucleation and crystallization at the buried interface are enhanced, the SCTF can grow thinner and more closely bonded to the substrate, and carrier recombination induced by interface defects and corresponding trap states is effectively suppressed. In addition, the energy barrier between the interfaces is also optimized, thereby promoting the transmission of carriers on the buried interface. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 (A) is a schematic diagram of the growth process of SCTF and the buried interface; (B) is a physical picture of the back side of SCTF grown on a PTAA substrate.

[0025] Figure 2(A) is a schematic diagram of the preparation of ITO / SAM / PTAA-SAM substrate; (B) is the element distribution diagram of ITO / SAM / PTAA-SAM substrate tested by ToF-SIMS; (CG) is the FTIR, Raman and XPS test diagram of PTAA and Meo-2PACz molecules on the substrate; (HI) is the hydrophobicity test diagram of different substrates.

[0026] Figure 3 (A) is the FTIR spectra of Meo-2PACz and PbI2; (B) is a schematic diagram of SCTF grown on ITO / SAM / PTAA-SAM substrate; (C) is a physical picture of the back side of SCTF grown on TO / SAM / PTAA-SAM substrate.

[0027] Figure 4 (A, B) are SEM cross-sectional images of the crystal morphology and quality characterization grown on two different substrates; (C, D) are AFM buried interface images; (E, F) are HRTEM buried interface images; (G) TRPL test characterizes the crystal quality.

[0028] Figure 5 (A) is a Cf test diagram that characterizes the photoelectric properties of crystals grown on two different substrates; (B) is a SCLC test diagram; (C) is an EIS test diagram; (D, E) are UPS tests and energy level arrangement diagrams; (F) is a TRPL test diagram that characterizes carrier transport.

[0029] Figure 6 (A) and (B) are the forward / reverse JV curve scans of perovskite single crystal cell devices based on PTAA-SAM substrate and PTAA substrate respectively; (C) is the EQE test graph of two different substrate devices; (D) is the efficiency statistics graph of two different substrate devices. DETAILED DESCRIPTION

[0030] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments, but the protection scope and implementation methods of the present invention are not limited thereto.

[0031] Unless otherwise specified, the materials and reagents used in the following examples are commercially available.

[0032] Example 1

[0033] A method for preparing a perovskite single crystal thin film comprises the following steps:

[0034] (1) Spin-coating a Meo-2PACz molecular solution dissolved in ethanol on an ITO glass pretreated with UV light, and annealing on a heating table at 100°C for 10 min to obtain a multilayer Meo-2PACz small molecule film; the concentration of the Meo-2PACz molecular solution was 0.5 mg / mL; the spin-coating speed was 3000 rpms, and the spin-coating time was 30 s;

[0035] (2) Spin coating a PTAA solution dissolved in chlorobenzene on the multilayer Meo-2PACz molecular film and annealing at 100°C for 10 min; the concentration of the PTAA solution is 1 mg / mL, and the molecular weight of PTAA is 5000; the rotation speed during spin coating is 4000 rpms, and the spin coating time is 30 s.

[0036] The growth process of SCTF (MAPbI3) and the growth model of PTAA interface are as follows: Figure 1 As shown in A, the surface chemical properties of the growth substrate largely determine the morphology and crystallinity of SCTF.

[0037] Due to the low surface energy of PTAA, there will be more voids at the interface between SCTF and PTAA, resulting in uneven interface and crystal desorption from the substrate. In addition, different types of defects will appear, such as growth dislocation. Figure 1 B is a physical picture of SCTF grown on a PTAA substrate, which corresponds to the growth model assumed in the present invention.

[0038] Since the self-assembled organic small molecule Meo-2PACz has a high carrier extraction ability, can effectively modulate the energy barrier, and has a certain interaction relationship with SCTF, it has broad development prospects in the field of high-performance SCTF optoelectronic devices. In order to suppress the interface carrier loss during the SCTF growth process and retain the advantages of PTAA at the same time, the present invention proposes an ITO / SAM / PTAA-SAM model for SCTF growth (such as Figure 2 A).

[0039] like Figure 2 As shown in B, the incorporation of SAM molecules into the PTAA layer was confirmed by time-of-flight secondary ion mass spectrometry (ToF-SIMS) analysis.

[0040] Due to the wrapping of PTAA and the interaction between MeO-2PACz molecules and PTAA ( Figure 2 C and 2D), XPS spectroscopy showed that the SAM molecules embedded in the PTAA layer can be well preserved during the long-term and high-temperature crystal growth process ( Figure 2E). During the growth of SCTF, some Meo-2PACz small molecules detached from the substrate due to being unable to withstand long-term immersion in high-temperature solution ( Figure 2 F and 2G), and the ITO / SAM / PTAA-SAM manufacturing mode of the growth substrate designed by the present invention has obvious advantages in preventing small molecules from escaping. The hydrophobic effect of PTAA is also retained in the PTAA-SAM layer, which is conducive to the growth of a single crystal film with a large area and suitable for preparing optoelectronic devices ( Figure 2 H and 2I).

[0041] Meo-2PACz small molecules can effectively interact with the uncoordinated electrons in Pb atoms and combine with PbI6-3 in the solution. From the Fourier transform infrared (FTIR) spectrum, it can be seen that the vibration peak of the P-OH bond in the Meo-2PACz small molecule mixed with PbI2 has a relative shift, proving that there is an interaction relationship between the Meo-2PAC small molecule and the Pb atom ( Figure 3 A). This interaction can provide sufficient perovskite nucleation sites on the surface of PTAA-SAM substrate, thus promoting the anisotropic lateral growth of SCTFs and suppressing defects and voids at the buried interface ( Figure 3 B and 3C).

[0042] Based on SCTF with a lateral size of about 2 mm, the present invention first studies the role of PTAA-SAM substrate in controlling the morphology of SCTF by promoting anisotropic lateral growth. Since there are sufficient nucleation sites on the surface of the PTAA-SAM substrate, the total thickness of the SCTF based on PTAA-SAM can be effectively reduced by 8 to 10 μm ( Figure 4 A and 4B). The reduction of SCTF thickness can suppress the imbalance of hole and electron transport caused by excessive single crystal thickness. The Meo-2PACz molecules embedded in the PTAA layer also promote the morphology and crystallization quality of the SCTF buried interface. -3 This will promote the nucleation of perovskite and the crystallization at the interface, thereby improving the buried interface in SCTF. From the atomic force microscopy (AFM) images, it can be seen that the buried interface of SCTF based on PTAA exhibits a higher roughness of 3.39nm ( Figure 4 C). In comparison, the buried interface of PTAA-SAM exhibits a lower roughness of about 0.37 nm ( Figure 4 D). In addition, the crystal quality of the buried interface was investigated using high-resolution transmission electron microscopy (HRTEM). Some crystal growth dislocation defects were observed in the buried interface of the PTAA-based SCTF, while the PTAA-SAM-based SCTF exhibited a more ordered lattice arrangement ( Figure 4 E and 4F). Time-resolved photoluminescence (TRPL) spectra of the SCTF buried interface show that the SCTF based on PTAA-SAM has a longer carrier lifetime than that based on PTAA ( Figure 4 G), indicating the reduction of interfacial non-radiative recombination, which is consistent with the interfacial crystalline quality measured by HRTEM.

[0043] The quality of the crystal is characterized by converting the density of trap states into a function of energy level depth through capacitance-frequency (Cf) measurement. The trap state distribution curve confirms that deep energy level traps with energy levels greater than 0.45 eV are suppressed in optoelectronic devices based on PTAA-SAM substrates, corresponding to the reduction of interface defects that lead to deep traps ( Figure 5 A). In addition, space charge limiting current (SCLC) measurements were used to quantify the trap state density on the surfaces of the two crystals. The trap filling limit (VTFL) voltages of single crystal devices based on PTAA and PTAA-SAM (both with a thickness of 20 μm) were 5 V and 0.72 V, respectively. The trap state density of the corresponding devices was calculated to be 4.4×10 13 cm -3 and 6.3×10 12 cm -3 ( Figure 5 B). It can be seen that the trap state density is reduced by about one order of magnitude in the device based on the PTAA-SAM substrate. The dynamics of carrier recombination caused by defect-induced traps was studied by electrochemical impedance spectroscopy (EIS). In a dark environment, the Nyquist plots of the two single-crystal cell devices characterized by EIS showed that the recombination resistance of the PTAA-SAM-based device (about 6 kΩ) was significantly higher than that of the PTAA-based device (about 3 kΩ), indicating that the carrier loss of the device was reduced ( Figure 5 C). In addition to reducing the density of trap states at the buried interface, the optimized substrate can also promote carrier transport by adjusting the interface energy level barrier. Ultraviolet photoelectron spectroscopy (UPS) is used to accurately characterize the energy level structure at each level. By anchoring a monolayer of Meo-2PACz on ITO, the work function of the ITO substrate is adjusted from -4.60eV to -5.05eV. Since the valence band maximum value of PTAA is -5.10eV, the energy level barrier between ITO and PTAA is effectively reduced, thereby promoting the transport of carriers at the interface ( Figure 5 D and 5E). The present invention uses TRPL to characterize the single crystals grown in situ on two substrates and studies the dynamics of carrier transmission at the interface ( Figure 5F). The results show that the carrier transport based on ITO / SAM / PTAA-SAM substrate (6.42ns) has a faster PL decay than the carrier transport based on ITO / PTAA substrate (11.61ns), which is consistent with the characterization results of the energy level in the present invention. Since the energy level barrier is optimized, the excited carriers can be quickly transferred instead of accumulating at the interface or causing carrier loss due to uneven carrier transport.

[0044] The present invention prepares a series of perovskite single crystal photovoltaic devices based on PTAA-SAM and PTAA substrates, and statistically analyzes the photoelectric conversion efficiency ( Figure 6 D) Figure 6 As shown in A and 6B, the present invention found that the device prepared using the PTAA-SAM substrate has better performance, and the efficiency of the optimal device reached 23.05% (the open circuit voltage VOC, short circuit current JSC and fill factor FF of the device are 1.131V, 25.01mA cm -2 and 81.5%, which are better than the best device prepared using PTAA substrate (the best efficiency of the device prepared based on PTAA substrate is 20.75%, the VOC of the device is 1.106 V, and the JSC is 23.93 mA cm -2 , FF is 78.4%). Compared with the single crystal device prepared on PTAA substrate, the hysteresis effect exhibited by PTAA-SAM substrate is greatly reduced, and Figure 6 The EQE test shown in C shows that the devices prepared on the PTAA-SAM substrate have enhanced external quantum efficiency at all absorption wavelengths. These enhanced photovoltaic performances are attributed to the multifunctionalization of the substrate, which suppresses the losses caused by non-radiative recombination at the interface.

[0045] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a perovskite single crystal thin film, characterized in that: The following steps are involved: (1) Spin coating a Meo-2PACz molecular solution dissolved in an organic solvent 1 on an ITO substrate, and annealing at 95-100° C. for 10-12 min to obtain a multilayer Meo-2PACz small molecule film; (2) Spin-coat the PTAA solution dissolved in organic solvent 2 onto the multilayer Meo-2PACz small molecule film and anneal at 95-100° C. for 10-12 min.

2. The method for preparing a perovskite single crystal thin film according to claim 1, characterized in that: In step (1), the concentration of the Meo-2PACz molecular solution is 0.5-5 mg / mL.

3. The method for preparing a perovskite single crystal thin film according to claim 1, characterized in that: In step (1), the ITO substrate is pretreated with UV.

4. The method for preparing a perovskite single crystal thin film according to claim 1, characterized in that: In step (1), the rotation speed during spin coating is 2000-3000 rpms, and the spin coating time is 20-30s.

5. The method for preparing a perovskite single crystal thin film according to claim 1, characterized in that: The organic solvent 1 includes ethanol or isopropanol, and the organic solvent 2 includes chlorobenzene or toluene.

6. The method for preparing a perovskite single crystal thin film according to claim 1, characterized in that: In step (2), the concentration of the PTAA solution is 1-5 mg / mL.

7. The method for preparing a perovskite single crystal thin film according to claim 1, characterized in that: In step (2), the rotation speed during spin coating is 4000-5000 rpms, and the spin coating time is 25-30s.

8. The method for preparing a perovskite single crystal thin film according to claim 1, characterized in that: In step (2), the molecular weight of the PTAA is 5000-25000.